2006
DOI: 10.1002/eat.20248
|View full text |Cite
|
Sign up to set email alerts
|

Girls with anorexia nervosa as young adults: Personality, self‐esteem, and life satisfaction

Abstract: Personality, self-esteem, and life satisfaction varied significantly between outcome groups. The results indicate that young patients with AN with a good outcome may have normal personality and self-esteem features in young adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 37 publications
6
45
0
4
Order By: Relevance
“…The combination of general dissatisfaction and perfectionism may be characteristic of patients with AN. 34,44 This may be reflected in a tendency to be critical and dissatisfied with both oneself and therapists.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of general dissatisfaction and perfectionism may be characteristic of patients with AN. 34,44 This may be reflected in a tendency to be critical and dissatisfied with both oneself and therapists.…”
Section: Resultsmentioning
confidence: 99%
“…31,34 The majority of patients replied that the hospital stay had been useful. The parents reported a high level of satisfaction with regard to the staff's care, competence, and collaboration during the hospital stay, but they had significantly lower scores concerning the support and information parents had received.…”
Section: Resultsmentioning
confidence: 99%
“…Concordant with these findings is the association between LS and AN. For example, a long-term follow up of childhood-and adolescent-onset females sufferers of AN in Norway showed significantly lower LS when compared to a sample of normal females (see Halvorsen and Heyerdahl 2006). Although found to have similar levels of self-esteem at follow up, former AN patients with no present eating disorder who had achieved normal eating attitudes had lower LS when compared to women in a large population study (Halvorsen and Heyerdahl 2006).…”
Section: Eating Disordersmentioning
confidence: 98%
“…The related to numerous negative psychological, personality, and behavioural factors, such as, neuroticism, perfectionism, negative self-evaluation, depression, and low self-esteem (Halvorsen and Heyerdahl 2006;Lombardi et al 1998). Similarly, research has shown adolescent LS to be negatively associated to neuroticism (e.g.…”
Section: Eating Disordersmentioning
confidence: 99%
“…Given the impact of weight on self-evaluation, it is not surprising that anorexic individuals have been found to have lower levels of self-esteem and negative selfconcept when compared to control groups (Cooper & Turner, 2000;Iniewicz, 2005). Halvorsen and Heyerdahl (2006) found that despite treatment and time, former patients with anorexia regarded as having poor outcome had significantly lower levels of self-esteem and life satisfaction scores. Though all of these studies support the dynamics and efficacy of Fairburn's treatment model, the authors state that additional research is needed to continue evaluating the core psychopathology involved in the disorder.…”
Section: Introductionmentioning
confidence: 93%